Synthesis of Novel Triazolothione, Thiadiazole, Triazole and Oxadiazole Functionalized Tri-fluoromethylnaphthyridine Derivatives and their Anticancer Activity & Antimicrobial Activity - Betala, Sailu; Racha, Hanumandlu; Abba, Chiranjeevi (Asian Journal of Chemistry, 2020)
Novel triazolothione, thiadiazole, triazole and oxadiazole-tagged trifluoromethyl group containing naphthyridine derivatives (6a-l and 7a-d) were synthesized from 2-amino-6-(thiophen-2- yl)-4-(trifluoromethyl)nicotinonitrile (1) on treatment with acetophenone and obtained 2-phenyl-7-(thiophen-2-yl)-5-(trifluoromethyl)-1,8-naphthyridin-4-amine (2), compound 2 on reaction with bromoethylacetate and after that reaction with hydrazine hydrate and obtained carbohydrazide derivatives (4), compound 4 on reaction with different substituted phenyl isothiocyanates to obtain phenyl hydrazine carbothiamide derivatives (5). Compound 5 is independently reaction with NaOH, H2SO4 and N2H4·H2O to obtain triazolothione, thiadiazole, triazole-substituted naphthyridine derivatives (6a-l), respectively. The carbohydrazide compounds 4 on reaction with diverse substituted aromatic acids and obtained oxadiazole derivatives (7a-d). All the synthesized compounds (6a-l and 7a-d) were tested for anticancer activity against four cancer cell lines such as “HeLa-cervical cancer (CCL-2) COLO 205-colon cancer (CCL-222) HepG2-liver cancer (HB-8065) MCF7-breast cancer (HTB-22) and one normal cell line (HEK 293)”. Compounds 6b, 6d and 6l are known to have good anticancer activity at micro molar concentration and found to be non-toxic on normal cell line. And all the products 6a-o and 7a-d were tested against Gram-positive, Gram-negative bacteria and fungal strains. All the compounds, compounds 6e-h showed more activity against Bacillus subtilis (MTCC-121) at < 6.8 micromolar concentration. Compounds (which showed more activity) further screened for minimum bactericidal concentration against B. subtilis MTCC 121 using ciprofloxacin as standard and known to show optimistic activity. These compounds further tested for biofilm inhibition activity against B. subtilis MTCC 121 using erythromycin as standard which confirmed the high activity.